High-stability quantum dot adhesive film and preparation method thereof

By adding 0.5-2 wt% of dodecyl mercaptan zinc to the photovoltaic film, the problem of quantum dot material being susceptible to water and oxygen during use is solved, and quantum dot efficiency is achieved stability and prolong the life of the adhesive film.

CN119505721APending Publication Date: 2025-02-25SHANGHAI XIANGUANG APPLIED MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411560104.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The water vapor transmittance of EVA and POE materials in existing photovoltaic films is high, which leads to the quantum dot materials being susceptible to water and oxygen erosion during use, resulting in deterioration of luminescence performance and affecting working life.

Method used

Add 0.5-2 wt% of dodecyl mercaptan zinc to the quantum dispensing film as a protective additive, and form a dense "protective sleeve" by coordinating with metal ions on the surface of the quantum dot to prevent water and oxygen molecules from being blocked by coordinating with the metal ions on the surface of the quantum dots. diffusion.

Benefits of technology

Effectively block the erosion of quantum dots by water and oxygen, maintain the stability of quantum dot efficiency, and extend the service life of the quantum dot film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117648620000031
    Figure BDA0005117648620000031
  • Figure BDA0005117648620000091
    Figure BDA0005117648620000091
  • Figure BDA0005117648620000101
    Figure BDA0005117648620000101
Patent Text Reader

Abstract

The invention belongs to the technical field of thin film material preparation, and particularly relates to a high-stability quantum dot adhesive film and a preparation method thereof. The content of the zinc dodecyl mercaptide in the quantum dot adhesive film is 0.5 to 2 weight percent. According to the light conversion adhesive film, the zinc dodecyl mercaptide is added into the light conversion adhesive film, so that the quantum dots are protected, and the stability of the quantum dots is improved. In the processing process, based on the dendritic structure of the zinc dodecyl mercaptide, the zinc dodecyl mercaptide can be coordinated with metal ions on the surfaces of the quantum dots, a compact and complex-structure'protective sleeve 'is formed on the surfaces of the quantum dots, water and oxygen molecules are prevented from being diffused into the quantum dots, the purpose of protecting the quantum dots is achieved, and therefore the stability of the quantum dots is improved, and the quantum dots are prepared. Therefore, the service life of the quantum dot adhesive film is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thin film material preparation, and in particular relates to a highly stable quantum dot adhesive film and a preparation method thereof. Background Art

[0002] In the current photovoltaic power generation industry, P-type silicon power generation technology represented by emitter passivation and rear contact (PERC) technology has gradually reached its efficiency limit (-24.5%). Compared with P-type silicon, N-type silicon has a longer carrier lifetime, and photovoltaic cells based on N-type silicon have higher photoelectric conversion efficiency. Heterojunction (HJT or HIT) technology, as a representative technology for N-type silicon power generation, has a limit efficiency of up to 27.5%. However, the absorption of ultraviolet rays by the TCO layer and the amorphous silicon passivation layer results in a low response of HJT cells to ultraviolet and short-wave radiation, making their current lower than the PERC current.

[0003] Affected by the long carrier life of N-type silicon, HJT cells have a higher theoretical conversion efficiency than PERC cells. However, the absorption of ultraviolet light by the TCO layer and amorphous silicon passivation layer in HJT cells makes their current smaller. By using fluorescence down-conversion technology to convert ultraviolet light into visible light that can be efficiently used by HJT cells, the spectral responsiveness of the cell can be enhanced, further improving the photoelectric conversion efficiency of the cell.

[0004] Quantum dots have the advantages of high fluorescence efficiency and high stability, and therefore have great application potential in the field of photovoltaic light conversion. However, the surface atoms of quantum dots easily react with water and oxygen, resulting in increased defect density and light quenching, which causes irreversible decay of the luminescence performance of quantum dots and affects the working life. Among the current photovoltaic films, the water vapor permeability of EVA films is relatively high. Although the water vapor permeability of POE films is only 1 / 8 of that of EVA films, there are still great risks for quantum dot materials.

[0005] CN107534075A discloses a quantum dot stabilized by a metal thiol polymer, which increases the QY and thermal stability of the quantum dot beads or composites by adding zinc thiol polymers to quantum dot-containing beads or composites. However, in this method, the zinc thiol polymer is used as the main material of the quantum dot to synthesize the quantum dot-(metal-thiol polymer) composite material, and its addition amount is higher than 10%, and the zinc thiol polymer is used as a thermal stabilizer to stabilize the quantum dot-(metal-thiol polymer) composite material to maintain a higher proportion of initial QY after processing. The composite film used by the quantum dot-(metal-thiol polymer) composite material still needs to block the penetration of oxygen and water vapor through two layers of barrier films, and cannot be applied to the field of photovoltaic adhesive films.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a highly stable quantum dot adhesive film and a preparation method thereof. The quantum dot adhesive film prepared by the method of the present invention can block the corrosion of water and oxygen on quantum dots during long-term use, thereby maintaining the stability of quantum dot efficiency, that is, the long-term stability of application.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A highly stable quantum dot adhesive film, wherein the content of zinc dodecyl mercaptan in the quantum dot adhesive film is 0.5-2wt%.

[0010] In the present invention, there is no need to process the quantum dots. Meanwhile, zinc dodecyl mercaptan is directly added only as a protective additive in an amount of 0.5-2wt%. The prepared quantum dot adhesive film can block the corrosion of water and oxygen on the quantum dots during long-term use, thereby maintaining the stability of the quantum dot efficiency, that is, the long-term stability of the application.

[0011] Furthermore, the quantum dots are one or more of CdSe, CdS, CdZnSe, CdZnS, CdZnSeS, CdSe / ZnS, CdSe / CdZnS, CdZnSe / ZnS, CdZnSe / CdZnS, CdSe / ZnSe, ZnSe / ZnS, and CdSe / CdZnS / ZnS.

[0012] The present invention also provides a method for preparing the quantum dot adhesive film, which comprises the following steps:

[0013] 1) preparing zinc dodecyl mercaptan;

[0014] 2) mixing the quantum dots, zinc dodecyl mercaptan and blank particles, and performing melting, extrusion and granulation to obtain masterbatch particles with light conversion effect;

[0015] 3) The masterbatch particles, blank particles, crosslinking agent, auxiliary crosslinking agent, coupling agent, light stabilizer and antioxidant are uniformly mixed, and then melt-extruded and cast to obtain the quantum dot adhesive film with high stability.

[0016] Furthermore, the process of preparing zinc dodecyl mercaptan in step 1) is: dissolving zinc salt and ammonia water to form a transparent zinc-based complex, and then directly reacting with dodecyl mercaptan at a certain temperature to prepare zinc dodecyl mercaptan; the reaction temperature is 65-85°C.

[0017] Furthermore, the zinc salt is any one of zinc oxide, zinc chloride, zinc acetate and zinc sulfate.

[0018] Furthermore, in step 2), the mass ratio of quantum dots to zinc dodecyl mercaptan is 1:0.5-1:2, preferably 1:1.

[0019] Furthermore, in step 2), the temperature of the feeding section, the extrusion section and the discharge section of the granulator is 70-120°C, preferably 80-100°C.

[0020] Furthermore, in step 3), the proportion of each component is as follows:

[0021]

[0022] Furthermore, in step 2) and step 3), the blank particles are one of EVA and POE.

[0023] Further,

[0024] The cross-linking agent is one or more of tert-butyl peroxy-2-ethylhexyl carbonate, 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and tert-amyl peroxy-2-ethylhexyl carbonate;

[0025] The auxiliary cross-linking agent is one or more of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, triallyl cyanurate, ethoxymethylpropane triacrylate, and propoxy trimethylolpropane triacrylate;

[0026] The silane coupling agent is one or more of γ-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltriethoxysilane, and γ-glycidyloxypropyltrimethoxysilane;

[0027] The light stabilizer is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate;

[0028] The antioxidant is one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], tris[2.4-di-tert-butylphenyl] phosphite, bis(2.4-di-tert-butylphenyl) pentaerythritol diphosphite, tris(nonylphenyl) phosphite, and triphenyl phosphite.

[0029] Furthermore, in step 3), the temperature of the feeding section, extrusion section and discharge section of the extruder is 70-120°C, preferably 80-100°C; the temperature in the tape casting process is 120-150°C, and the thickness of the film is 0.2-0.5mm.

[0030] Compared with the prior art, the present invention has the following advantages:

[0031] The present invention protects quantum dots by adding zinc dodecyl mercaptan to the light-converting adhesive film, thereby improving the stability of the quantum dots. During the processing, based on the dendritic structure of zinc dodecyl mercaptan, zinc dodecyl mercaptan can coordinate with metal ions on the surface of the quantum dots to form a dense and complex "protective cover" on the surface of the quantum dots, which prevents water and oxygen molecules from diffusing into the quantum dots, thereby protecting the quantum dots, thereby improving the stability of the quantum dots and extending the service life of the quantum dot adhesive film. DETAILED DESCRIPTION

[0032] The following are specific embodiments of the present invention, and the embodiments are intended to further describe the present invention rather than to limit the present invention.

[0033] Example 1

[0034] 1) preparing zinc dodecyl mercaptan;

[0035] Take 4.1g zinc oxide and add it to 25g deionized water, stir it evenly to form zinc oxide slurry, slowly inject the zinc oxide slurry into 50g ammonia solution, and stir until the solution is clear. Then add 50ml dodecyl mercaptan and 5ml ethanol, heat the solution to 80℃, react for 4h, and then cool the solution to 35℃. Centrifuge the cooled solution with ethanol and deionized water, filter it, repeat three times, and vacuum dry it to obtain white dodecyl mercaptan zinc solid powder.

[0036] 2) Take 20g of CdZnS / ZnS quantum dots, 20g of zinc dodecyl mercaptan and 160g of EVA particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 110°C, 115°C and 120°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2 mm are finally obtained.

[0037] 3) Take 100g (10%) masterbatch particles, 889g (88.9%) EVA particles, 5g (0.5%) crosslinking agent tert-butyl peroxy-2-ethylhexyl carbonate, 4g (0.4%) co-crosslinking agent trimethylolpropane triacrylate, 1g (0.1%) silane coupling agent vinyl tris (β-methoxyethoxy) silane, 0.5g (0.05%) antioxidant 2,2'-methylenebis (4-methyl-6- tert-butylphenol), 0.5g (0.05%) light stabilizer bis(1,2,2,6,6-pentamethylpiperidinol) sebacate were mixed evenly and poured into an extruder. The temperatures of the feed section, extrusion section and discharge section of the extruder were set to 110°C, 115°C and 120°C respectively. After melt extrusion, the temperature was raised to 140°C, and the molten raw material was injected into a mold. After cast molding, a light-converting film with a film thickness of 0.4 mm was finally obtained.

[0038] Example 2

[0039] 1) preparing zinc dodecyl mercaptan;

[0040] Take 13.2g of zinc acetate and add it to 25g of deionized water, stir it evenly to form a zinc acetate solution, slowly inject the zinc acetate solution into 50g of ammonia solution, and stir until the solution is clear. Then add 50ml of dodecyl mercaptan and 5ml of ethanol, heat the solution to 65℃, react for 4h, and then cool the solution to 40℃. Centrifuge the cooled solution with ethanol and deionized water, filter it by suction, repeat three times, and vacuum dry it to obtain a white solid powder of dodecyl mercaptan zinc.

[0041] 2) Take 20g of CdZnSeS quantum dots, 20g of zinc dodecyl mercaptan and 160g of POE particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 80°C, 85°C and 90°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2 mm are finally obtained.

[0042] 3) Take 200g (20%) of masterbatch particles, 710g (71%) of POE particles, 30g (3%) of crosslinking agent tert-butyl peroxy-2-ethylhexyl carbonate, 20g (2%) of auxiliary crosslinking agent trimethylolpropane triacrylate, 20g (2%) of silane coupling agent vinyl tri(β-methoxyethoxy) silane, 10g (1%) of antioxidant triphenyl phosphite, 10g (1%) of light stabilizer sebacate bis(1,2,2,6,6-pentamethylpiperidinol) ester and mix them evenly, then pour them into an extruder, and the temperatures of the feed section, extrusion section and discharge section of the extruder are set to 80°C, 85°C and 90°C respectively. After melt extrusion and heating to 120°C, the molten raw material is injected into a mold, and after cast molding, a light-converting film with a film thickness of 0.2 mm is finally obtained.

[0043] Example 3

[0044] 1) preparing zinc dodecyl mercaptan;

[0045] Take 6.8g of zinc chloride and add it to 25g of deionized water, stir it evenly to form zinc chloride slurry, slowly inject the zinc chloride slurry into 50g of ammonia solution, and stir until the solution is clear. Then add 50ml of dodecyl mercaptan and 5ml of ethanol, heat the solution to 85℃, react for 4h, and then cool the solution to 38℃. Centrifuge the cooled solution with ethanol and deionized water, filter it by suction, repeat three times, and vacuum dry it to obtain white solid powder of dodecyl mercaptan zinc.

[0046] 2) Take 20g of CdSe quantum dots, 20g of zinc dodecyl mercaptan and 160g of EVA particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 110°C, 115°C and 120°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2 mm are finally obtained.

[0047] 3) Take 150g (15%) masterbatch particles, 817g (81.7%) EVA particles, 10g (1%) crosslinking agent 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane, 8g (0.8%) co-crosslinking agent triallyl isocyanurate, 5g (0.5%) silane coupling agent γ-(methacryloyloxy)propyl trimethoxysilane, 5g (0.5%) antioxidant β-(3,5-di-tert-butyl-4 -hydroxyphenyl) propionic acid octadecyl ester and 5g (0.5%) light stabilizer bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate were mixed evenly and poured into an extruder. The temperatures of the feed section, extrusion section and discharge section of the extruder were set to 70°C, 75°C and 80°C respectively. After melt extrusion, the temperature was raised to 150°C, and the molten raw material was injected into a mold. After cast molding, a light-converting film with a film thickness of 0.5 mm was finally obtained.

[0048] Example 4

[0049] 1) preparing zinc dodecyl mercaptan;

[0050] Take 4.1g zinc oxide and add it to 25g deionized water, stir it evenly to form zinc oxide slurry, slowly inject the zinc oxide slurry into 50g ammonia solution, and stir until the solution is clear. Then add 50ml dodecyl mercaptan and 5ml ethanol, heat the solution to 70℃, react for 4h, and then cool the solution to 36℃. Centrifuge the cooled solution with ethanol and deionized water, filter it by suction, repeat three times, and vacuum dry it to obtain white dodecyl mercaptan zinc solid powder.

[0051] 2) Take 20g of CdSe / CdZnS / ZnS quantum dots, 20g of zinc dodecyl mercaptan and 160g of EVA particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 110°C, 115°C and 120°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2 mm are finally obtained.

[0052] 3) Take 50g (5%) masterbatch particles, 900g (90%) EVA particles, 28g (2.8%) crosslinking agent 2,5-dimethyl-2,5-bis (tert-butylperoxy) hexane, 12g (1.2%) co-crosslinking agent trimethylolpropane trimethacrylate, 8g (0.8%) silane coupling agent vinyl trimethoxysilane, 1g (0.1%) antioxidant tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid ] After pentaerythritol ester and 1g (0.1%) light stabilizer poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) ester are mixed evenly, the mixture is poured into an extruder, and the temperatures of the feed section, extrusion section and discharge section of the extruder are set to 110°C, 115°C and 120°C respectively. After melt extrusion and heating to 140°C, the molten raw material is injected into a mold and subjected to cast molding to finally obtain a light-converting film with a film thickness of 0.4 mm.

[0053] Example 5

[0054] 1) preparing zinc dodecyl mercaptan;

[0055] Take 8.2g of zinc sulfate and add it to 25g of deionized water, stir it evenly to form a zinc sulfate solution, slowly inject the zinc sulfate solution into 50g of ammonia solution, and stir until the solution is clear. Then add 50ml of dodecyl mercaptan and 5ml of ethanol, heat the solution to 82°C, react for 4h, and then cool the solution to 38°C. Use ethanol and deionized water to centrifuge the cooled solution, filter it by suction, repeat three times, and vacuum dry it to obtain a white solid powder of dodecyl mercaptan zinc.

[0056] 2) Take 20g of CdSe / CdZnS quantum dots, 20g of zinc dodecyl mercaptan and 160g of EVA particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 110°C, 115°C and 120°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2 mm are finally obtained.

[0057] 3) Take 120g (12%) masterbatch particles, 814g (81.4%) EVA particles, 20g (2%) crosslinking agent peroxy-2-ethylhexyl carbonate tert-amyl ester, 18g (1.8%) co-crosslinking agent triallyl tricyanate, 16g (1.6%) silane coupling agent vinyl triethoxysilane, 6g (0.6%) antioxidant 2,2'-thiobis [3-(3,5-di-tert-butyl-4-hydroxy After being evenly mixed, the mixture was poured into an extruder. The temperatures of the feed section, extrusion section and discharge section of the extruder were set to 110°C, 115°C and 120°C respectively. After melt extrusion and heating to 140°C, the molten raw material was injected into a mold and subjected to cast molding to finally obtain a light-converting film with a thickness of 0.4 mm.

[0058] Example 6

[0059] 1) preparing zinc dodecyl mercaptan;

[0060] Take 4.1g zinc oxide and add it to 25g deionized water, stir it evenly to form zinc oxide slurry, slowly inject the zinc oxide slurry into 50g ammonia solution, and stir until the solution is clear. Then add 50ml dodecyl mercaptan and 5ml ethanol, heat the solution to 80℃, react for 4h, and then cool the solution to 37℃. Centrifuge the cooled solution with ethanol and deionized water, filter it, repeat three times, and vacuum dry it to obtain white dodecyl mercaptan zinc solid powder.

[0061] 2) Take 20g of CdSe / ZnSe quantum dots, 20g of zinc dodecyl mercaptan and 160g of EVA particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 110°C, 115°C and 120°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2mm are finally obtained.

[0062] 3) Take 200g (20%) masterbatch particles, 750g (75%) EVA particles, 14g (1.4%) crosslinking agent tert-butyl peroxy-2-ethylhexyl carbonate, 12g (1.2%) co-crosslinking agent ethoxymethyl propane triacrylate, 16g (1.6%) silane coupling agent γ-glycidyl ether oxygen propyl trimethoxy silane, 4g (0.4%) antioxidant tris [2.4-di-tert-butylphenyl] phosphite, 4g (0.4%) light stabilizer sebacate bis (1,2,2,6,6-pentamethylpiperidinol) ester and mix them evenly, then pour them into an extruder, the feed section, extrusion section and discharge section temperatures of the extruder are set to 110° C., 115° C. and 120° C. respectively, after melt extrusion and heating to 140° C., the molten raw material is injected into a mold, and after cast molding, a light-converting film with a film thickness of 0.4 mm is finally obtained.

[0063] Example 7

[0064] 1) preparing zinc dodecyl mercaptan;

[0065] Take 4.1g zinc oxide and add it to 25g deionized water, stir it evenly to form zinc oxide slurry, slowly inject the zinc oxide slurry into 50g ammonia solution, and stir until the solution is clear. Then add 50ml dodecyl mercaptan and 5ml ethanol, heat the solution to 80℃, react for 4h, and then cool the solution to 35℃. Centrifuge the cooled solution with ethanol and deionized water, filter it, repeat three times, and vacuum dry it to obtain white dodecyl mercaptan zinc solid powder.

[0066] 2) Take 20g of CdZnSe / CdZnS quantum dots, 40g of zinc dodecyl mercaptan and 160g of EVA particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 110°C, 115°C and 120°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2 mm are finally obtained.

[0067] 3) Take 121g (12.1%) masterbatch particles, 800g (80%) EVA particles, 26g (2.6%) crosslinking agent tert-butyl peroxy-2-ethylhexyl carbonate, 24g (2.4%) co-crosslinking agent propoxy trimethylolpropane triacrylate, 14g (1.4%) silane coupling agent vinyl tri(β-methoxyethoxy) silane, 7.5g (0.75%) antioxidant bis(2.4-di-tert-butylphenyl) Pentaerythritol diphosphite and 7.5g (0.75%) of light stabilizer bis(1,2,2,6,6-pentamethylpiperidinol) sebacate were mixed evenly and poured into an extruder. The temperatures of the feed section, extrusion section and discharge section of the extruder were set to 110°C, 115°C and 120°C respectively. After melt extrusion, the temperature was raised to 140°C, and the molten raw material was injected into a mold. After cast molding, a light-converting film with a film thickness of 0.4 mm was finally obtained.

[0068] Example 8

[0069] 1) preparing zinc dodecyl mercaptan;

[0070] Take 4.1g zinc oxide and add it to 25g deionized water, stir it evenly to form zinc oxide slurry, slowly inject the zinc oxide slurry into 50g ammonia solution, and stir until the solution is clear. Then add 50ml dodecyl mercaptan and 5ml ethanol, heat the solution to 80℃, react for 4h, and then cool the solution to 40℃. Centrifuge the cooled solution with ethanol and deionized water, filter it by suction, repeat three times, and vacuum dry it to obtain white dodecyl mercaptan zinc solid powder.

[0071] 2) Take 20g of CdZnSe / ZnS quantum dots, 10g of zinc dodecyl mercaptan and 160g of EVA particles, mix them evenly, and add them into a twin-screw extruder granulator. The temperatures of the feed section, extrusion section and discharge section of the granulator are set to 110°C, 115°C and 120°C, respectively. After melting, extrusion, wire drawing and pelletizing, masterbatch particles with a particle size of 2 mm are finally obtained.

[0072] 3) 180g (18%) of masterbatch particles, 770g (77%) of EVA particles, 25g (2.5%) of crosslinking agent tert-butyl peroxy-2-ethylhexyl carbonate, 16g (1.6%) of co-crosslinking agent trimethylolpropane triacrylate, 7.4g (0.74%) of silane coupling agent vinyl tris (β-methoxyethoxy) silane, 0.8g (0.08%) of antioxidant tris (nonylphenyl) phosphite, 0.8g (0.08%) of light stabilizer bis (1,2,2,6,6-pentamethylpiperidinol) sebacate were mixed evenly and poured into an extruder. The temperatures of the feed section, extrusion section and discharge section of the extruder were set to 110° C., 115° C. and 120° C., respectively. After melt extrusion and heating to 140° C., the molten raw material was injected into a mold and cast to finally obtain a light-converting film with a film thickness of 0.4 mm.

[0073] Example 9

[0074] Referring to Example 1, the difference from Example 1 is that the quantum dots used in step 2) are CdS.

[0075] Example 10

[0076] Referring to Example 1, the difference from Example 1 is that the quantum dots used in step 2) are CdZnSe.

[0077] Embodiment 11

[0078] Referring to Example 1, the difference from Example 1 is that the quantum dots used in step 2) are CdZnS.

[0079] Example 12

[0080] Referring to Example 1, the difference from Example 1 is that the quantum dots used in step 2) are CdSe / ZnS.

[0081] Example 13

[0082] Referring to Example 1, the difference from Example 1 is that the quantum dots used in step 2) are ZnSe / ZnS.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 1 is that no zinc dodecyl mercaptan is added in step 2).

[0085] Test Example 1

[0086] This test example investigates the effect of the amount of zinc dodecyl mercaptan on the stability of the prepared quantum dot film.

[0087] Test method: The quantum dot film was prepared according to the method of Example 1, except that the amount of zinc dodecyl mercaptan was changed, as shown in Table 1. The stability of the quantum dot film prepared with different amounts of zinc dodecyl mercaptan was investigated.

[0088] Detection method:

[0089] The photovoltaic glass is stacked in the order of photovoltaic glass, upper light-converting adhesive film, solar cell, lower light-converting adhesive film and lower photovoltaic glass from bottom to top, and then placed in a vacuum laminator. After evacuation for 10 minutes, the temperature is raised to 120°C and laminated at a pressure of 25 MPa to obtain a photovoltaic module.

[0090] The quantum dot adhesive films prepared by using different amounts of zinc dodecyl mercaptan were used as light-converting adhesive films (upper light-converting adhesive film and lower light-converting adhesive film), and photovoltaic modules were obtained after lamination according to the above method. The initial power generation and DH1000h power of the obtained photovoltaic modules were measured respectively, and the attenuation rate was calculated and compared to obtain the following test data:

[0091] The results are shown in Table 1:

[0092] Table 1

[0093]

[0094]

[0095] DH stands for high temperature and high humidity aging. The test adopts a temperature of 85°C and a humidity test environment of 85%, and the power generation efficiency of the battery component is tested after 1000 hours. Attenuation refers to the power attenuation of the battery component after 1000 hours of high temperature and high humidity aging.

[0096] The above results show that the amount of zinc dodecyl mercaptan added to the film has a certain effect on the initial power generation and stability of the battery assembly. When the amount of zinc dodecyl mercaptan added is 5g-20g, the initial power generation of the assembly is not much different, and the attenuation is small after 1000h of wet heat aging. It shows that under the protection of zinc dodecyl mercaptan, the film is gradually less affected by water and oxygen in the environment, and the film is more stable. When the amount of zinc dodecyl mercaptan added continues to increase, although the attenuation of the assembly power generation is still reduced, too much zinc dodecyl mercaptan affects the light conversion effect of the quantum dots, resulting in a decrease in the initial efficiency of the assembly.

[0097] Test Example 2

[0098] This test example investigated the effect of adding zinc dodecyl mercaptan on the stability of the prepared quantum dot film.

[0099] Detection method:

[0100] The photovoltaic glass is stacked in the order of photovoltaic glass, upper light-converting adhesive film, solar cell, lower light-converting adhesive film and lower photovoltaic glass from bottom to top, and then placed in a vacuum laminator. After evacuation for 10 minutes, the temperature is raised to 120°C and laminated at a pressure of 25 MPa to obtain a photovoltaic module.

[0101] The quantum dot adhesive films prepared in Example 1 and Comparative Example 1 were respectively used as light conversion adhesive films (including an upper light conversion adhesive film and a lower light conversion adhesive film), and laminated according to the above method to obtain photovoltaic modules. The initial power generation and DH1000h power of the photovoltaic modules were measured respectively, and the attenuation rate was calculated and compared to obtain the following test data:

[0102] Table 2

[0103] Initial power (W) DH1000h power (W) Decay rate Example 1 446.7 438.7 -1.78% Comparative Example 1 444.1 415.9 -6.35%

[0104] It can be seen from the results in Table 2 that, compared with the quantum dot adhesive film prepared without adding zinc dodecyl mercaptan, the quantum dot adhesive film prepared by adding zinc dodecyl mercaptan in the present invention has better stability.

Claims

1. A highly stable quantum dot adhesive film, characterized in that: The content of zinc dodecyl mercaptan in the quantum dot adhesive film is 0.5-2wt%.

2. The quantum dot adhesive film according to claim 1, characterized in that: The quantum dots are one or more of CdSe, CdS, CdZnSe, CdZnS, CdZnSeS, CdSe / ZnS, CdSe / CdZnS, CdZnSe / ZnS, CdZnS / ZnS, CdZnSe / CdZnS, CdSe / ZnSe, ZnSe / ZnS, and CdSe / CdZnS / ZnS.

3. A method for preparing a quantum dot adhesive film according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: 1) preparing zinc dodecyl mercaptan; 2) mixing the quantum dots, zinc dodecyl mercaptan and blank particles, and performing melting, extrusion and granulation to obtain masterbatch particles with light conversion effect; 3) The masterbatch particles, blank particles, crosslinking agent, auxiliary crosslinking agent, coupling agent, light stabilizer and antioxidant are uniformly mixed, and then melt-extruded and cast to obtain the quantum dot adhesive film with high stability.

4. The preparation method according to claim 3, characterized in that: Step 1) The process of preparing zinc dodecyl mercaptan is as follows: dissolving zinc salt and ammonia water to form a transparent zinc-based complex, and then directly reacting with dodecyl mercaptan at a certain temperature to prepare zinc dodecyl mercaptan; the reaction temperature is 65-85°C.

5. The preparation method according to claim 3, characterized in that: In step 2), the mass ratio of the quantum dots to zinc dodecyl mercaptan is 1:0.5-1:2, preferably 1:

1.

6. The preparation method according to claim 3, characterized in that: In step 2), the temperature of the feeding section, the extrusion section and the discharge section of the granulator is 70-120°C, preferably 80-100°C.

7. The preparation method according to claim 3, characterized in that: In step 3), the proportion of each component is as follows:

8. The preparation method according to claim 3, characterized in that: In step 2) and step 3), the blank particles are one of EVA and POE.

9. The preparation method according to claim 7, characterized in that: The cross-linking agent is one or more of tert-butyl peroxy-2-ethylhexyl carbonate, 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and tert-amyl peroxy-2-ethylhexyl carbonate; The auxiliary cross-linking agent is one or more of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, triallyl cyanurate, ethoxymethylpropane triacrylate, and propoxy trimethylolpropane triacrylate; The silane coupling agent is one or more of γ-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltriethoxysilane, and γ-glycidyloxypropyltrimethoxysilane; The light stabilizer is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate; The antioxidant is one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], tris[2.4-di-tert-butylphenyl] phosphite, bis(2.4-di-tert-butylphenyl) pentaerythritol diphosphite, tris(nonylphenyl) phosphite, and triphenyl phosphite.

10. The preparation method according to claim 3, characterized in that: In step 3), the temperature of the feeding section, extrusion section and discharge section of the extruder is 70-120° C., preferably 80-100° C.; the temperature in the tape casting process is 120-150° C., and the thickness of the film is 0.2-0.5 mm.

Citation Information

Patent Citations

  • Quantum dots stabilized with a metal thiol polymer

    CN107534075A